(untitled) (Experimental biology, 2025)
This article examines ecosystem services and economic importance of mammals in the Irtysh River floodplain ecosystem and assesses the degree of anthropogenic disturbances in the region. We conducted field observations from February to October 2023 which included tracking mammal activity and assessing biodiversity across seven sectors within two areas, the Black Irtysh and the Pavlodar Irtysh in the north and northeast of Kazakhstan. We found that 87 mammalian species inhabiting the Irtysh River valley provide 245 ecosystem services. The greatest contribution to the ecosystem services provided is presented by Rodents (65.7%), as the order with the largest number of species found in the region. Services such as Pest control and The animal and human populations’ health are ensured, for the most part, by Carnivores and Insectivores (37% and 31.5%, respectively), while Soil fertility is largely regulated by Cetartiodactyls (33%). Many ecosystem services are provided by rare and game mammal species. Based on calculations of their economic value, we determined that the damage from the loss of each number of game and rare species of mammals in the two study areas amounted to 43,392,445 tenge. Considering the economic and touristic potential of these species, the entire length of the Irtysh floodplain in Kazakhstan has high economic importance. As a result of the principal component analysis (PCA) and calculation of the anthropogenic disturbance index (ADI), we found that the ADI index for the Black Irtysh sectors is significantly lower (1.15±0.1) than for the Pavlodar Irtysh (1.84±0.17). Sector 3 in Black Irtysh has the least human disturbance and can be considered the most significant for the conservation of biodiversity in the region. In general, mammals in the Irtysh River floodplain provide important ecosystem services and are of high economic and ecosystem importance. The presence of anthropogenic disturbance in the region indicates the need to create strategies for the conservation and rational use of mammals of the Irtysh River floodplain, including mitigating the consequences of environmental degradation and human activities.